Highly Enantioselective Synthesis of Phosphorus‐Containing ϵ‐Benzosultams by Bifunctional Phosphonium Salt‐Promoted Hydrophosphonylation. Issue 44 (30th June 2021) - Zhang, Song; Feng, Zhenghuai; Jiang, Chunhui; Yu, Xiaojun; Pan, Jianke; Du, Juan; Jiang, Zhiyu; Chen, Yuan; Wang, Tianli
Abstract: ϵ‐Benzosultam derivatives are potential drug candidates with diverse biological activities. A series of chiral ϵ‐benzosultams bearing phosphorus functionalities was synthesized by catalytic asymmetric hydrophosphonylation in the presence of a bifunctional phosphonium salt catalyst. The desired hydrophosphonylation products were obtained in good yields with high enantioselectivities, and scale‐up reactions and further derivations were successfully accomplished. Some control experiments were also conducted to elucidate the plausible reaction mechanism of this chemical transformation. Abstract : The crucial ingredients : The first highly enantioselective hydrophosphonylation of seven‐membered cyclic N ‐sulfonyl imines by bifunctional phosphonium salt catalysis has been developed, and a broad range of optically pure phosphorus‐containing ϵ‐benzosultam compounds was readily prepared under mild conditions with very low catalyst loading, easy purification and high yields. The practicality and utility of this protocol were demonstrated by scaled‐up reactions and facile synthetic elaborations. The mechanistic results suggested that the ion‐pair and H‐bonding interactions were crucial in asymmetric induction.